2009
DOI: 10.1158/0008-5472.can-08-4113
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 Induces Tumor Cell Survival via Nuclear Factor-κB–Dependent Induction of EGR1 Transcription in Prostate Cancer Cells

Abstract: Transcription factor E2F1 has been implicated in both apoptosis-promoting and apoptosis-suppressing effects. However, factors that mediate its antiapoptotic effects are still not identified. Using prostate tumor-derived cell lines, we showed here that E2F1 activated the expression of transcription factor EGR1 for promoting cell survival. E2F1 up-regulated the production of EGR1-induced growth factors, epidermal growth factor, platelet-derived growth factor, and insulin-like growth factor II, which in turn acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 47 publications
1
39
0
1
Order By: Relevance
“…To understand the molecular mechanism of PCAF-dependent apoptosis resistance, we investigated genes related to tumor cell survival in cisplatin-resistant cells and PCAF-overexpressing cells. E2F1 has an antiapoptotic function (23)(24)(25) and is acetylated and stabilized by PCAF (16). As expected, E2F1 expression was upregulated in cisplatin-resistant cells and FIGURE 5.…”
Section: Discussionsupporting
confidence: 60%
“…To understand the molecular mechanism of PCAF-dependent apoptosis resistance, we investigated genes related to tumor cell survival in cisplatin-resistant cells and PCAF-overexpressing cells. E2F1 has an antiapoptotic function (23)(24)(25) and is acetylated and stabilized by PCAF (16). As expected, E2F1 expression was upregulated in cisplatin-resistant cells and FIGURE 5.…”
Section: Discussionsupporting
confidence: 60%
“…EGR1 or early growth response 1 is a zinc finger protein that has been reported to possess both oncogenic and tumor suppressor properties. Zheng et al have shown that NFkBinduced EGR1 transcription allowed survival of prostate tumor cells, whereas other authors have suggested a proapoptotic role by induction of Bax (37,38). ATF3, or activating transcription factor 3, is a leucine zipper protein involved in cellular stress pathways.…”
Section: Discussionmentioning
confidence: 99%
“…2, Table III and Table SI), tumor suppressor genes or TFs regulating tumor suppressors were identified for all of the entities including expression of FOXO1 [22] in FL cells, PA2G4 [23] in DLBCL cells, SOX11 [24] in MCL cells, and PRDM2 [25] in CLL. Furthermore, SOX4 and EGR1, known depending on tumor type, to act both as tumor suppressors [26][27][28][29] and oncogenes [30,31] showed lower expression in CLL cells. Finally, HCL cells had a high expression of SOX4, and also a low expression of FOXP1 [32].…”
Section: B-cell Lymphoma Entities Express Unique Sets Of Transcriptiomentioning
confidence: 97%